Система нічного бачення на базі відеокамер Hikvision - Медведєв, Є. О.; Михайлов, Д. О. (ХНУРЕ, 2025)
The report is dedicated to the integration of video surveillance cameras as a night vision system in military vehicles. Traditional lighting, particularly head lights, can reveal the vehicle's location, creating a risk for the crew during com bat operations. Specialized night vision systems are expensive and not widely available, and standard devices have limitations, such as strong glare and low range. The use of cameras, such as Hikvision models, provides a modern, cost effective, and efficient solution that enables combat operations under limited visibility conditions without using visible light.
Keywords: система нічного бачення; відеокамера Hikvision